Utility of EMG Logger in diagnose sleep bruxism - Le, Thi Khanh Huyen; Nguyen, Gia Kieu Ngan (Tạp chí Y Dược Huế, 2025)
Background: Surface electromyographic (EMG) devices are becoming more and more popular to assess sleep bruxism. Objectives: To evaluate characteristics of sleep bruxism using EMG Logger. Materials and Methods: A convenient sample of the patients at Hue University of Medicine and Pharmacy Hospital who had clinical signs related to sleep bruxism was collected. The patients were asked for anamnesis, followed by clinical examination and then guided to attach EMG Logger device in 2 consecutive nights, recorded data were analyzed by a specialized software. Results: Severe sleep bruxism accounts for the highest rate of 67%, moderate level accounts for 33%, there is no mild level and no bruxism; 80% had tooth wear, buccal and tongue mucosa ridging were 83.3% and 93.3%, respectively, there is no difference between the level of sleep bruxism and clinical signs (p > 0.05); 82.9% were phasic and mixed episode, 17.1% were tonic episode. Conclusions: EMG Logger supports diagnose and provide detailly about specifications of sleep bruxism.